Clinical characteristics and management of Haglund’s disease: comparison of conservative and surgical approaches - Oliveira , Mateus Bueno de Pinho; Ferreira Outi, Hayani Yuri; De Melo Oliveira, Rullya Marson; Silva Oliveira, Marcos Aurélio; Souza Neto, Vilton; Barcelos, Paulo Henrique; Araújo Rufino, José Henrique (Journal of the Foot & Ankle, 2026)
Objective: To compare the clinical characteristics and outcomes of surgical approaches in the management of Haglund’s disease, to provide a comprehensive view of therapeutic options, and guide clinical decision-making. Methods: The search was conducted in PubMed, Scopus, and Embase, covering studies published up to July 2024. Clinical studies comparing conservative treatment, such as physical therapy and/or orthoses, with surgical intervention, including endoscopic and open calcaneoplasty, were included. The quality of the studies was evaluated using the PRISMA guidelines, and the data synthesis was performed qualitatively and quantitatively. Results: Thirteen studies were included, totaling 1,375 patients. Conservative treatments were effective in up to 70% of cases, with a 30% recurrence rate. Surgical interventions, especially endoscopic calcaneoplasty, showed pain relief in more than 85% of patients, with lower recurrence rates (10%) and fewer complications than open surgery. Conclusion: Surgical interventions, particularly endoscopic ones, are more effective and associated with lower complication and recurrence rates than conservative treatments. However, the therapeutic decision must be individualized, taking into account the severity of symptoms and the patient’s preferences. Level of evidence I